2024
DOI: 10.1002/osp4.732
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based care needs for adults with class III obesity before and after tertiary weight management: An exploratory study

Jillian Termaat,
Milan K. Piya,
Kate A. McBride

Abstract: ObjectiveClass 3 obesity (severe obesity) is defined by a body mass index ≥40 kg/m2. Tertiary weight‐management programs (WMPs) are hospital‐based multidisciplinary services that aim to support individuals with severe obesity. Severe shortage of WMPs has led to waitlists and pressure on clinicians to discharge patients. Community obesity management often fails to support patients in maintaining weight loss/health gains. This study aimed to explore the needs of patients for community‐based obesity care.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Despite these limitations, due to the simplicity and convenience of data collection, this study used BMI as a measure of obesity. Previous qualitative research has also suggested that mental health, stigma, and social isolation impact engagement with community-based services [47]. While the baseline QoL scores have been used to try and predict weight loss after bariatric surgery [48], to the author's knowledge, there is no current research on the psychological predictors of mental health outcomes following non-surgical weight management interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, due to the simplicity and convenience of data collection, this study used BMI as a measure of obesity. Previous qualitative research has also suggested that mental health, stigma, and social isolation impact engagement with community-based services [47]. While the baseline QoL scores have been used to try and predict weight loss after bariatric surgery [48], to the author's knowledge, there is no current research on the psychological predictors of mental health outcomes following non-surgical weight management interventions.…”
Section: Introductionmentioning
confidence: 99%